Komodifikasi Agama dalam Gerakan Majlis Tafsir Al-Qur’an (MTA) di Surakarta - Zaki Faddad; Anisatul Mardiah (Religió: Jurnal Studi Agama-agama, 2020)
This paper aims to describe the process of religious commodification within Majlis Tafsir Al-Qur’an (MTA) in Surakarta. The teaching and practices of MTA (such as the doctrine of salvation, leadership and brotherhood, and the practice of pengajian) have effectively constructed social belonging among its members. It represents the production of social identity, loyalty, and solidarity. Besides, the charisma of its leader, Ahmad Sukino, has become a center of social appeal. Social belonging and charisma become influential elements for the MTA members. One of the MTA compelling-doctrines is the doctrine of jihad harta. It occurs through mobilizing the contribution of MTA members and commodifying pengajian. Referring to Kitiarsa (2010), there are at least two reasons behind this religious commodification: commodity and market. MTA monetizes religion-based objects, such as brochures, books, and videos. Pengajian becomes a market where the process of commodification follows.